Cardiac resynchronisation therapy in chronic atrial fibrillation: impact on left atrial size and reversal to sinus rhythm - Kiès, P (BMJ Group, 2006)
OBJECTIVE: To evaluate the impact of long term cardiac resynchronisation therapy (CRT) on left atrial and left ventricular (LV) reverse remodelling and reversal to sinus rhythm (SR) in patients with heart failure with atrial fibrillation (AF). PATIENTS: 74 consecutive patients (age 68 (8) years; 67 men) with advanced heart failure and AF (20 persistent and 54 permanent) were implanted with a CRT device. MAIN OUTCOME MEASURES: Patients were evaluated clinically (New York Heart Association (NYHA) class, quality of life, six minute walk test) and echocardiographically (LV ejection fraction, LV diameters, and left atrial diameters) before and after six months of CRT. Additionally, restoration of SR was evaluated after six months of CRT. RESULTS: NYHA class, quality of life score, six minute walk test, and LV ejection fraction had improved significantly after six months of CRT. In addition, left atrial and LV end diastolic and end systolic diameters had decreased from 59 (9) to 55 (9) mm, from 72 (10) to 67 (10) mm, and from 61 (11) to 56 (11) mm, respectively (all p < 0.01). During implantation 18 of 20 (90%) patients with persistent AF were cardioverted to SR. At follow up 13 of 18 (72%) patients had returned to AF and none had spontaneously reverted to SR; thus, only 5 of 74 (7%) were in SR. CONCLUSION: Six months of CRT resulted in significant clinical benefit with significant left atrial and LV reverse remodelling. Despite these beneficial effects, 93% of patients had not reverted to SR.